2020
DOI: 10.1186/s13073-020-00740-7
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and tissue-specific expression of endogenous retroelements in human somatic tissues

Abstract: Background: Endogenous retroelements (EREs) constitute about 42% of the human genome and have been implicated in common human diseases such as autoimmunity and cancer. The dominant paradigm holds that EREs are expressed in embryonic stem cells (ESCs) and germline cells but are repressed in differentiated somatic cells. Despite evidence that some EREs can be expressed at the RNA and protein levels in specific contexts, a systemlevel evaluation of their expression in human tissues is lacking. Methods: Using RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 87 publications
2
60
0
Order By: Relevance
“…Considered for a long time as "junk" DNA, the remnants of retroelements still contains functional promoters, enhancers, ORFs, splice donor/acceptor sites and polyadenylation sites able to impact cell physiology (85) and can contribute to several key processes of our development and adulthood (86)(87)(88). In line with this, Larouche et al recently reported that various levels of ERE transcripts can be found in all human somatic tissues and that their expression is particularly predominant in mTECs which are responsible for T cell negative selection (89). These findings suggest that some antigens derived from these "domesticated" EREs are tolerated by the immune system.…”
Section: Endogenous Retroelements-derived Tumor-specific Antigens: a mentioning
confidence: 91%
See 1 more Smart Citation
“…Considered for a long time as "junk" DNA, the remnants of retroelements still contains functional promoters, enhancers, ORFs, splice donor/acceptor sites and polyadenylation sites able to impact cell physiology (85) and can contribute to several key processes of our development and adulthood (86)(87)(88). In line with this, Larouche et al recently reported that various levels of ERE transcripts can be found in all human somatic tissues and that their expression is particularly predominant in mTECs which are responsible for T cell negative selection (89). These findings suggest that some antigens derived from these "domesticated" EREs are tolerated by the immune system.…”
Section: Endogenous Retroelements-derived Tumor-specific Antigens: a mentioning
confidence: 91%
“…These aeERE have been reported to affect cancer progression through both pro-and antitumoral mechanisms (95). Previous reports indicated that aeERE could generate viral-like neoantigens able to increase both the antigenicity and immunogenicity of tumor cells (89,94). Unlike the ERE-derived antigens expressed in normal tissues, those restricted to cancer cells (i.e., aeEREs) can be recognized by the immune system although they originate from non-mutated sequences.…”
Section: Endogenous Retroelements-derived Tumor-specific Antigens: a mentioning
confidence: 99%
“…This concept has important implications. First, annotated exons represent only 2% of the genome and many allegedly non-protein coding (non exonic) sequences are coding for proteins and do generate MAPs [23][24][25][26]. Second, epigenetic and splicing aberrations in cancer cells lead to the appearance of numerous proteins and MAPs that are not found in normal cells.…”
Section: Neoantigens and The Fallacy Of The Conversementioning
confidence: 99%
“…In contrast to MS analyses, transcriptomic analyses have been performed in many subjects on practically all cell types. Hence, when we identify aeTSA candidates, we evaluate whether its coding transcript is found in normal tissues from the GTEx database (https://gtexportal.org/home/) or in our datasets of mTECs [26]. We believe that inclusion of mTECs in the "negative controls" is important for three reasons: i) they orchestrate central immune tolerance [66], ii) they express much higher levels of MHC I molecules than other epithelial cell types [48], and iii) they promiscuously express more genes than other types of somatic cells [67,68].…”
Section: Strategies For Ms-based Identification Of Aetsasmentioning
confidence: 99%
See 1 more Smart Citation